153k views
3 votes
2(x + 6) = - 5x - 16.

User Mbochynski
by
4.7k points

2 Answers

4 votes
ANSWER: x = -4

Explanation: if you use distributive property with the parentheses it leaves you with 2x + 12 which the equation will then change to 2x+12 = -5x-16 you then subtract the 12 to the -16..

after that the equation would change to 2x = -5x-28 then now what you would do it add the 5x to the 2x and would get 7x...


after that the equation would then change to 7x = -28 you would then divide by 7 and that would bring up the answer of -4.

Hope this helps
5 votes

Answer:
x=-4

Simplify both sides of the equation


(2)(x)+(2)(6)=-5x+-16(Distribute)\\2x+12=-5x+-16

Add 5x to both sides


2x+12+5x=-5x-16+5x\\7x+12=-16

Subtract 12 from both sides


7x+12-12=-16-12\\7x=-28

Divide both sides by 7


7x/7=-28/7\\x=-4

User Miguel Reyes
by
4.5k points